Speech processing for makhraj recognition (design adaptive filter for noise removal) - Siti Nurmaisarah, Abdul Aziz (2010)
Processing for MAKHRAJ Recognition is a topic that very useful in many applications and environments in our daily day to improve MAKHRAJ for Arabic alphabets. In this project, it needs to design Adaptive Filter for noise removal. There are 30 Arabic, أ until ي but for this project, only 7 Arabic will be used as samples, أ until خ. The speech processing will be used to obtain same waveform output from two different situations, road and cafeteria. Least Mean Square (LMS) Algorithm based on Adaptive Filter technique is used to remove noise. Filter Design Toolbox provides many adaptive filter design functions that use the LMS algorithms to search for the optimal solution to adaptive filter, including system identification and noise cancellation. The filtered data will be processed to match the standard pronunciations and it will be integrated with filter design process in MATLAB. As a result, the noise will be removing and produce same waveform signal.